Energetic and Exergetic Performances of a Retrofitted, Large-Scale, Biomass-Fired CHP Coupled to a Steam-Explosion Biomass Upgrading Plant, a Biorefinery Process and a High-Temperature Heat Network - Roeland De Meulenaere (MDPI AG, 2021)
This paper aims at assessing the impact of retrofitting an existing, 730 MW<semantics>e</semantics>, coal-fired power plant into a biomass-fired combined heat and power (CHP) plant on its energetic and exergetic performances. A comprehensive thermodynamic model of the power plant was developed and validated against field data, resulting in less than <semantics>1%</semantics> deviation between the model and the measurements for the main process parameters. The validated model was then used to predict the behaviour of the biomass CHP after retrofitting. The modelled CHP unit is coupled to a steam-explosion biomass upgrading plant, a biorefinery process, and a high-temperature heat network. 13 scenarios were studied. At constant boiler load, delivering heat to the considered heat clients can increase the total energy efficiency of the plant from <semantics>44%</semantics> (electricity only) to <semantics>64%</semantics>, while the total exergy efficiency decreases from <semantics>39%</semantics> to <semantics>35%</semantics>. A total energy efficiency of <semantics>67%</semantics> could be reached by lowering the network temperature from <semantics>120<mspace width="3.33333pt"></mspace>∘</semantics>C to <semantics>70<mspace width="3.33333pt"></mspace>∘</semantics>C. Identifying the needed heat clients could, however, represent a limiting factor to reach such high efficiencies. For a constant power demand, increasing the boiler load from 80 to <semantics>100%</semantics> in order to provide additional heat makes the total energy efficiency increase from <semantics>43%</semantics> to <semantics>55%</semantics>, while the total exergy efficiency decreases from <semantics>39%</semantics> to <semantics>36%</semantics>.